Decadence Disrupted: Arguing Against a Decadence Model in Late Ming Painting History. (May 2015) - Burnett, Katharine P.
Abstract : This essay offers an intervention to the field of Chinese art history, arguing that a decadence model has been tacitly operating in studies of late Ming painting, and that this model has clouded our understanding of this art. A possible source of the decadence model is explained, and a few of the terms resulting from its application are contemplated. A number of historical fallacies that have combined with the decadence model are identified, and are brought to bear in a cautionary note to beware of confusing cause for correlation.